Karakterisasi Material Karbon Aktif Dari Pelepah Nipah (Nypa Fruticans) Dengan Metode Aktivasi Kimia - Rosita Dwityaningsih; Ilma Fadlilah; Ayu Pramita (P3M Politeknik Negeri Cilacap, 2024)
Nypa Palm fronds has a high lignocellulose, so it has potential to be used as activated carbon. In this research, activated carbon will be made from Nypa palm fronds using H3PO4 as activator and heated at high temperature. The aim of this research is to know about characterisation of activated carbon from Nypa palm fronds with H3PO4. Activated carbon from Nypa palm fronds was made by 2 M H3PO4 and the carbon powder siz was 80 mesh. It was found that activated carbon from nipa palm fronds has characteristic that are in accordance with technical activated carbon requiremet of SNI 06-3730-1995. It has water content of 3%, ash content of 7,25%, iodine absorbance 1129.41 milligrams per gram, methylene blue absorbance 123.99 milligrams per gram and contains the functional groups C=C and P-O-P. Additional pores can be seen on the surface of the activated carbon when compared to carbon without activation.